From Silk Thread to Melodies - ใจเหิม อังคณา (Journal of Educational Review Faculty of Education in MCU, 2018)
This article aims to present the composition of songs applied with Thai musical theories and principles of Thai composition as guidelines to create the melodies in harmony with the characteristics of each type of regional silk weaving. It is an independent composition with new melodies from the researcher’s imagination under rules and regulations of Thai composition. The music is created from sounds of folk music rhyme with the imaginative melodies abiding by rhythms, musical techniques and traditional practices of Thai classical composition. It is found that the Jok Fabric Song is mixed between the Northern Thailand and the Chinese melodies. Its melody proceeds with skipping rhythm technique, flinging technique like main silk line snatching up and down and minor silk line whipping and silk line knitting with one another and becoming fabric design. This song is a combination of Thai musical performance and Thai handicraft composed of melody translation, melody coordination with sound relation principle, innovated pattern musical instrument coordination for melody procession, and unity of song created by harmony between the rhythm and melody patterns and the silk weaving techniques.